Preliminary report of intra-ovarian injections of autologous platelet-rich plasma (PRP) in extremely poor prognosis patients with only oocyte donation as alternative: a prospective cohort study. Issue 4 (22nd June 2022) - Barad, D H; Albertini, D F; Molinari, E; Gleicher, N
Abstract: STUDY QUESTION: Does intraovarian injection of platelet-rich plasma (PRP) change ovarian function in patients with extremely low functional ovarian reserve who otherwise likely only have a chance of pregnancy through third-party oocyte donation? SUMMARY ANSWER: No clinically significant effects of PRP treatment on ovarian function were observed over one year of follow-up. WHAT IS KNOWN ALREADY: Several investigators have reported improved responses to ovulation induction after treatment with PRP. However, previous published reports have involved, at most, only small case-series. Whether PRP actually improves ovarian performance is therefore still unknown. PRP is nevertheless widely offered as an "established" fertility treatment, often under the term "ovarian rejuvenation." STUDY DESIGN, SIZE, DURATION: We are reporting a prospective cohort study of 80 consecutive patients at ages 28-54 with low functional ovarian reserve (LFOR), defined by AMH < 1.1 ng/mL, FSH > 12 mIU/mL or at least one prior IVF cycle with ≤ 3 oocytes within one year. The women were followed for one year after an intraovarian PRP procedure. PARTICIPANTS/MATERIALS, SETTING, METHODS: PRP (1.5 ml) was injected into the cortex of ovaries with an average of 12 injections per ovary. Study participants were followed every three days for two weeks after PRP treatment with estradiol and follicle stimulating hormone (FSH) measurements and vaginal ultrasound to observe follicle growth and thereafter followed weekly. Beginning one month after their PRP treatment, participants underwent one or more cycles of ovarian stimulation for IVF. Outcome measures were endocrine response, and numbers of oocytes and embryos produced in response to a maximal gonadotropin stimulation before and after PRP treatment. MAIN RESULTS AND THE ROLE OF CHANCE: In this study women failed to demonstrate statistically significant outcome benefits from intra-ovarian PRP. However two 40-year-old very poor-prognosis patients, with prior failed IVF cycles that never reached embryo transfer at other centres, achieved pregnancy, resulting in an ongoing pregnancy rate of 4.7% among patients who, following PRP, produced at least one oocyte (n = 42). LIMITATIONS, REASONS FOR CAUTION: As an observational study of patients who performed poorly in past ovarian stimulation cycles, the improvement may be accounted for by regression to the mean. Similar considerations may also explain the occurrence of the two pregnancies. WIDER IMPLICATIONS OF THE FINDINGS: This study demonstrates that, even in extremely poor prognosis patients due to low functional ovarian reserve, sporadic pregnancies are possible. The study, however, does not allow for the conclusion that those pregnancies were the consequence of PRP treatments. A case series, indeed, does not allow for such conclusions, even if results are more suggestive than here. This registered study, therefore, must be viewed as a preliminary report, with further data expected from this study but also from two other prospectively randomized ongoing registered studies with more controlled patient selection. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by intramural funds from The Center for Human Reproduction and the not-for-profit research Foundation for Reproductive Medicine, both in New York, N.Y., USA. Drs. Gleicher and Barad are listed as co-inventor on several U.S. patents. Some of these patents relate to pre-supplementation of hypo-androgenic infertile women with androgens, such as DHEA and testosterone and, therefore, at least peripherally relate to the subject of this manuscript. They, as well as Dr. Albertini, have also received research support, travel funds and speaker honoraria from several pharmaceutical and medical device companies, though none related to the here presented subject and manuscript. Dr. Gleicher is a shareholder in Fertility Nutraceuticals and he and Dr. Barad receive royalty payments from Fertility Nutraceuticals LLC. Dr Molinari has no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: NCT04275700